2015
DOI: 10.1093/fampra/cmv051
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care quality and hospitalizations for ambulatory care sensitive conditions in the public health system in Porto Alegre, Brazil

Abstract: Better quality of health care services, in a setting of overwhelmingly low quality services not adapted to the care of chronic conditions, did not influence the rate of avoidable hospitalizations, while social and demographic characteristics, especially non-white ethnicity and lesser schooling, indicate that social inequities play a predominant role in health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 16 publications
2
17
0
15
Order By: Relevance
“…However, the authors confirmed the indicator's applicability for comparing different regions or to make regional comparisons, as long as health insurance coverage was considered and allowed the identification of possible differences in provision of primary health care services. Gonçalves et al 30 , using a validated instrument for evaluation of primary health care -PCATool Brazil -in a cohort study in Porto Alegre, Rio Grande do Sul State, found that improvement in the supply of public healthcare services did not influence the admissions rate for PCSCs in a context of previously limited services supply. Finally, a study in Espírito Santo State, Brazil, using bivariate analysis, found a positive association between coverage of the FHP/FHS and admissions for PCSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors confirmed the indicator's applicability for comparing different regions or to make regional comparisons, as long as health insurance coverage was considered and allowed the identification of possible differences in provision of primary health care services. Gonçalves et al 30 , using a validated instrument for evaluation of primary health care -PCATool Brazil -in a cohort study in Porto Alegre, Rio Grande do Sul State, found that improvement in the supply of public healthcare services did not influence the admissions rate for PCSCs in a context of previously limited services supply. Finally, a study in Espírito Santo State, Brazil, using bivariate analysis, found a positive association between coverage of the FHP/FHS and admissions for PCSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The study was motivated by the observation of high admissions rates for PCSCs in ered by the SUS, and explore the impact of closing a hospital on admissions rates for PCSCs, thereby contributing to an on-going debate on the indiscriminate use of this indicator for inferences on the expansion and quality of primary care 28,29,30 . The target period is 2006 to 2011, when coverage by the FHP/FHS in the municipality varied irregularly from approximately 65% to 71% (Índice de Desempenho do Sistema Único de Saúde.…”
Section: Introductionmentioning
confidence: 99%
“…A fonte dessa heterogeneidade tem como causas, entre outras, deficiências na formação profissional, déficits estruturais e baixa incorporação tecnológica. [7][8][9][10] A situação se repete na atenção secundária, com o agravante da insuficiência de pontos de atenção.…”
Section: Introductionunclassified
“…[17][18][19][20][21][22] Nevertheless, authors suggest caution in considering that, even with the established reduction of ICSAP, it is possible to find other determining factors besides the increase of primary care coverage and the ESF. [23][24] In fact, our study found a relationship between the ESF coverage and the increase in the number of registered hypertensive patients and the monitored ones in Mato Grosso do Sul, with no significant results regarding the reduction of harm and mortality due to hypertension in the State, 4 since the proportion of people with monitored hypertension when compared to the number of estimated in all groupings still does not reach the majority of patients (<50%).…”
mentioning
confidence: 99%